Pengaruh Perubahan Tutupan Lahan Terhadap Temperature Humadity Index di Kota Samarinda - Yuda Saifitulloh, Septia; Astha, Dwinsani Pratiwi; Mustofa, Umar; Kadri, Mohtana Kharisma (COMPACT: Spatial Development Journal, 2024)
The relocation of the State Capital (IKN) in East Kalimantan Province has the potential to increase the intensity of development in Samarinda City as a buffer city for the IKN as well as the city with the largest population. High urbanization leads to population growth and increased land demand which has an impact on land use change. However, the city of Samarinda currently does not meet the minimum standard of 30% of the green open space area. This is in line with the increase in temperature that occurs with a high risk of extreme weather disasters. High temperatures can affect the Temperature Humadity Index (THI), especially when the THI exceeds 26°C, which is the comfort limit. Therefore, analysis is needed to identify THI and land cover using image interpretation analysis techniques and multiple linear regression statistical analysis. THI for the last 10 years (2014 - 2023), the lowest value in 2014 and the highest in 2020. The t-test showed that the variable of built land with a value of 0.00 and vegetation with a value of 0.03 had an effect on THI. Keywords : Temperature Humadity Index, Land Cover, Green Open Space